Analysis on smart waste management in Malaysia - Abdullah Din, Ummi Nur Kamilah; Yusoff, Siti Hajar; Midi, Nur Shahida; Khan, Sheroz (2018)
Human overpopulation is among the most pressing environmental issues. As the population growth is rapidly increasing, there will be more people who will consume more resources. On the other hand, public waste bins are filling up faster than ever and inevitably, many of the bins end up overflowing before collected, causing not only cluttered streets and bad odors, but also negative health and environmental impacts. The question that everyone has in mind but not knows what the solution is, how to manage the issue of overflowing bins? To cater this problem, a new effective waste disposal management can be proposed. With the title of “Analysis on Smart Waste Management in Malaysia”, the objective of this research is mainly to conduct a survey that shows the current household waste management in Malaysia, to analyze the conducted survey and to propose a subtle solution for the garbage overflowing issues. This research will focus on the implementation of few sensors and microcontroller that act as the internet of things’ (IoT) devices in the dustbin. Of the biggest benefit to develop a smart waste management system is to notify the waste collector of the real-time status of the waste level inside a bin through short message services (SMS), which later will assign the waste collector crews to collect the waste inside the bin. This system will decrease the cost and increase the time efficiency of the services. In addition, this study is vital to provide statistical amount of waste collected in Malaysia within the stipulated time and to prevent overflow of the garbage from the unattended bins. Hence, it can lead to the prevention of environmental pollution.